Design and Development of a Feeding Control System for Fish in Cultivation Ponds - Novi Herawadi Sudibyo; Bayu Nugroho; Danang Ade; MS Hasibuan; Imam F; Riandi Riandi; Bayu Jalur (LPPM Universitas Islam 45 Bekasi, 2025)
Fish farming is one of the crucial sectors in supporting food security and the community's economy. However, one of the primary challenges faced by fish farmers is managing feed distribution efficiently and on time. This study aims to design and develop an automated fish feeding control system for cultivation ponds. The system is designed using a microcontroller as the central controller, equipped with a timer sensor and a motor to distribute feed according to a predefined schedule. Testing was conducted to measure the accuracy of feed distribution, the system's reliability under various environmental conditions, and its impact on fish growth. The results show that the developed system can provide feed automatically and consistently based on the set schedule, with a very low error rate in feed distribution. Additionally, the system improves feed utilization efficiency and minimizes waste, contributing to reduced operational costs. This automated control system is expected to be an effective solution to support fish farming activities, enhance productivity, and promote the adoption of technology in the aquaculture sector